If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 * 4 * -2 = x Multiply 3 * 4 12 * -2 = x Multiply 12 * -2 -24 = x Solving -24 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -24 + -1x = x + -1x Combine like terms: x + -1x = 0 -24 + -1x = 0 Add '24' to each side of the equation. -24 + 24 + -1x = 0 + 24 Combine like terms: -24 + 24 = 0 0 + -1x = 0 + 24 -1x = 0 + 24 Combine like terms: 0 + 24 = 24 -1x = 24 Divide each side by '-1'. x = -24 Simplifying x = -24
| 3x^3+3x-6x=0 | | -6x-12=10+5x | | s(t)=-t^3+13t^2-40t | | 3c+4=11c | | -18=3(-a+6)+2z | | (7x^2-8)+(3x^2+1)= | | 13-4z=2z+9 | | 2x+2=-3x+6 | | 2x+2=4x+-6 | | cos(7x+ln(5x))=0 | | lx^2+3x+1l=1 | | 9-3x+2=10-3x | | 20+0.07(x-20)=0.06x | | 3u^2+3v^2-6uv+20u-20v+12=0 | | 1x-3y=14 | | Xy-4x+10=0 | | 9x+11=5x+1 | | 20+0.07x=0.06x | | x+9+2x=30 | | 11+2a=14 | | 3p=60+8p | | .2(x+100)=10 | | (-12)+6/2= | | 59-6x=3x+16 | | 20x+50b=320 | | -3x-y=17 | | 120+12x=545 | | 9x-2-4x-13=30 | | 4x^2-100x+625=0 | | x^2+20x+225=0 | | 4x-1=15x+1 | | 7x-6=58 |